AN ALTERNATIVE DIGITAL FEEDBACK THROUGH SCREENCAST: BLENDED LEARNING PRACTICES ON ACADEMIC WRITING - Syifa Khuriyatuz Zahro (English Review: Journal of English Education, 2023)
Aiming at elucidating screencast use as alternative digital feedback in the academic writing class throughout blended learning, screencast was investigated in classroom action research with three cycles. The results discovered that screencast feedback was successfully implemented and evidenced to enhance students' writing skills. The success was proved by the higher number of students who passed the passing score as competent writers. Given screencast feedback, students found it was helpful, clear, and easy. Also, they felt an increased teacher-student interpersonal relation, improved teacher praise, and a conversation-like atmosphere during screencast feedback with an additional teacher’s visual presence. Several teachers’ reflections from each cycle were also discussed further. In short, screencast was implemented successfully in academic writing courses and was able to enhance students’ scientific article writing.